Amino acid-capped metal selenide nanoparticles: their synthesis, characterization, optical and magnetic properties - Mokubung, Kopano Edward (My University, 2018)
Quantum dots (QDs) have already proven features that can be considered to improve their properties for biological applications. Metal selenide nanoparticles possess semiconducting behaviors that can vary with structural and optical properties evolving from their synthesis. An aqueous medium through a simple, non-toxic and environmentally friendly colloidal route for the preparation of water-soluble CdSe, Cu2Se, FeSe semiconductor nanoparticles has been developed. Different capping molecules with multi-functional moieties (-COOH, -NH2 and -OH) namely, L-cysteine, L-glutamic acid and L-phenylalanine, have been employed in the preparation of cadmium selenide, copper selenide and iron selenide semiconductor nanoparticles as capping molecules. The synthesized metal selenide nanoparticles were characterized by Fourier Transform Infrared (FTIR), UV-Vis spectroscopy, Photoluminescence spectroscopy (PL), X-ray Diffraction (XRD), Vibrating Sample Magnetometer (VSM) and Transmission Electron Microscopy (TEM). The FTIR spectroscopy confirmed the binding moiety through the surface of the nanoparticles which is pH dependent. The XRD patterns confirmed a cubic phase of CdSe and Cu2Se while FeSe revealed a hexagonal phase for the synthesized nanoparticles. The optical absorption as a function of wavelength for the prepared nanoparticles at different temperature is investigated. The morphology of the nanoparticles dominated through this method was spherical in shape. Amino acids capped metal selenide nanoparticles were successfully synthesized by aqueous medium through a simple colloidal route. The absorption spectra of all samples prepared were blue shifted as compared to their bulk counterparts which signify quantum confinement effect. The optical absorption measurements show some dependency of the temperature values used in the synthesis of nanoparticles. The effect of temperature and pH on the growth and morphology of nanoparticles was investigated. X-ray diffraction patterns confirms the structure, single cubic and hexagonal phase for the synthesized nanoparticles. TEM studies of metal selenide nanoparticle show that particle size increases with the increase in reaction temperature. The vibrating sample magnetometer (VSM) shows almost linear without any hysteresis loop for copper selenide, which indicated the absence of magnetism and exhibits paramagnetic nature than diamagnetic properties while iron selenide revealed twofold ferromagnetic behavior in low fields and paramagnetic behavior in up fields.
M. Tech (Department of Chemistry, Faculty of Applied and Computer Sciences) Vaal University of Technology.
Keywords: Quantum dots, selenide, Photoluminescence spectroscopy, Vibrating Sample Magnetometer,Transmission Electron Microscopy; Amino acids.; Amino acids -- Synthesis.; Nanoparticles.